Penatalaksanaan Fisioterapi Pada Kasus Calcaneus Spurs BilateralDi RSUD Salatiga - Khafina, Iffa, Yulisna Mutia Sari, SST.FT. M.Sc (GRS) (2015)
Background : calcaneus spurs projection growth bone or formed on the bottom surface of the legs or spine calcaneus. The problems of physiotherapy in the form of pain in both heels, decreased muscle strength, then limited of activity day living (ADL). Methods : the methods in the management of in the case, using Ultra Sound (US), exercise, then evaluated using methods of measuring of muscle strength (MMT), ability of ADL (LEFS). Objectives :above methods to understand the benefites of US an exercise therapy in reducing pain, increasing range or motions, increasing muscle sterngth and increasing of ability ADL. Results :after had given physioterapy 6 times the results obstained : decreased of pain, increased range of motions ankle, increased muscl strength of ankle and then increased ability of functional activity. Conclusion :ultra sound can reduce pain, exercise therapy can increases range of motions, muscle strength and ability of functional activity.